2018
DOI: 10.14740/gr1045w
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous Granular Cell Tumor of the Descending Colon

Abstract: Granular cell tumors (GCTs) are uncommon tumors. They are believed to be neuronal in origin and are usually found in the head and/or neck area of the body. They have also been reported in various locations of the gastrointestinal (GI) system, usually discovered during routine screening colonoscopy. We report a case of GCT in a 58-year-old asymptomatic African American female as a metachronous tumor of a well-differentiated adenocarcinoma of the sigmoid colon, which was an incidental finding in screening colono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…6 The granular cell tumor, in this case, is a malignant granular cell tumor. We did not come to a malignant conclusion from the Fanburg-Smith criteria, as in the case reported by Shrestha, et al (2018), who concluded that the lesion was malignant not based on the Fanburg-Smith criteria. 16 Although microscopic observations based on the Fanburg-Smith criteria do not support malignancy, metastases indicate the nature of a granular cell tumor.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…6 The granular cell tumor, in this case, is a malignant granular cell tumor. We did not come to a malignant conclusion from the Fanburg-Smith criteria, as in the case reported by Shrestha, et al (2018), who concluded that the lesion was malignant not based on the Fanburg-Smith criteria. 16 Although microscopic observations based on the Fanburg-Smith criteria do not support malignancy, metastases indicate the nature of a granular cell tumor.…”
Section: Discussioncontrasting
confidence: 52%
“…15 Examination by electron microscopy will be seen as polygonal cells containing eosinophilic granules resembling Schwann cells. 16 The diagnosis of granular cell tumors is still being debated. There are three reasons why the diagnosis of this tumor is debatable.…”
Section: Discussionmentioning
confidence: 99%
“…GCTs are uncommon tumors. They are believed to be of neuronal origin ( 57 ). They are soft tissue tumors, which are thought to be derived from Schwann cells ( 58 ).…”
Section: Background: Evidence From Previous Animal Studiesmentioning
confidence: 99%
“…Macroscopical examination of GCT tumors reveals hard lesions, isolated with a mucosal nodule or covered with normal mucosa, not distinguishable from other gastrointestinal polyps. Hence, microscopical evaluation is diriment to decide if surgical treatment is necessary [4] , [11] , [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%